Implementasi Program Literasi di SDN 031 Banu-Banua Kabupaten Polewali Mandar - Noraffina Noraffina; Salam Salam; Baharman Baharman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to examine in depth the implementation of literacy programs at SDN 031 Banu-Banua, Polewali Mandar Regency which is carried out through three main stages, namely the stages of habituation, development, and learning. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. This approach is used to provide a comprehensive overview of the implementation of school literacy programs. The results of the study show that the implementation of the literacy program at SDN 031 Banu-Banua has gone well. At the habituation stage, the program succeeded in forming students' reading habits through routine activities such as reading Tuesday, reading corner, and Wednesday of faith. The development stage successfully expands students' literacy skills and analytical power through activities such as wall magazine management, book reflection, and visual literacy. The learning stage contributes to improving students' creativity, critical thinking skills, and communication skills through short story writing activities, story presentations, and work discussions. The success of the implementation of the program is supported by the active involvement of teachers and the availability of adequate literacy facilities. However, there are still several obstacles faced, including low interest in reading students, lack of variation in the reading atmosphere due to the absence of libraries, and the influence of undirected use of technology. Overall, the literacy program at SDN 031 Banu-Banua shows effectiveness in fostering a basic literacy culture in students. The implementation of this program needs to be strengthened through the procurement of school libraries, active involvement of parents, and the application of literacy methods that are more innovative and relevant to technological developments.